PENGARUH VARIASI PERMAINAN TERHADAP HASIL PASSING PADA SISWA EKSTRAKURIKULER FUTSAL DI SMA NEGERI 10 PONTIANAK - Nurhidayatim, Muhammad; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the Effect of Game Variations on Passing Results in Futsal Extracurricular Students of SMA Negeri 10 Pontianak. The purpose of this study was to determine the Effect of Game Variations on the Results of Passing in Futsal Extracurricular Students. The method used in this study was an experiment in the form of one group pre-test post-test design. The population and sample in this study were students who took extracurricular activities, amounting to 18 students. Data analysis with computerized systems and analysis using t-test. The results showed a pretest value of 0.176> 0.05 and posttest value of 0.322> 0.05. Analysis of the data obtained the value of t is equal to 10.95. The degree of freedom db = (N-1) is 18-1 = 17 and a significance level of 0.05 obtained the value of t table = 1.740, meaning that the hypothesis is accepted means that there is an influence of Variations on the Passing Results in Futsal Extracurricular Students.Â Keywords: Â Variation Of The Game, Passing